Peningkatan Pelatihan Dan Pengembangan Karir Terhadap Produktivitas Kerja Karyawan - Ifany Nursaumi; Faizal Mulia Z; Erry Sunarya (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
ABSTRACT This study aims to determine the effect of training and career development variables on work productivity. This study uses quantitative methods. The population in this study were employees of Hotel Santika Sukabumi City and the sample used was 38 respondents. The data analysis technique used is multiple linear regression analysis and the sample technique used is probability sampling. The results of this study indicate that simultaneously and partially the variables of training and career development have a positive and significant effect on work productivity. The results of the f test, which is known from the value of Fcount 43,798 > 3.27, shows that the value of Fcount is greater than Ftable and from the correlation results in this study, it has a strong and high value of 0.715. Meanwhile, from the results of the t-test value, namely Tcount 5.643 > 1689, it shows that Tcount is greater than Ttable so it can be concluded that the training and career development variables have an influence on work productivity. Keywords: Training, Career Development. Work Productivity